Insights into the ubiquitin-proteasome system of human embryonic stem cells - Saez, Isabel; Dieterich, Christoph (Scientific reports, 2018)
Human embryonic stem cells (hESCs) exhibit high levels of proteasome activity, an intrinsic characteristic required for their self-renewal, pluripotency and differentiation. However, the mechanisms by which enhanced proteasome activity maintains hESC identity are only partially understood. Besides its essential role for the ability of hESCs to suppress misfolded protein aggregation, we hypothesize that enhanced proteasome activity could also be important to degrade endogenous regulatory factors. Since E3 ubiquitin ligases are responsible for substrate selection, we first define which E3 enzymes are increased in hESCs compared with their differentiated counterparts. Among them, we find HECT-domain E3 ligases such as HERC2 and UBE3A as well as several RING-domain E3s, including UBR7 and RNF181. Systematic characterization of their interactome suggests a link with hESC identity. Moreover, loss of distinct up-regulated E3s triggers significant changes at the transcriptome and proteome level of hESCs. However, these alterations do not dysregulate pluripotency markers and differentiation ability. On the contrary, global proteasome inhibition impairs diverse processes required for hESC identity, including protein synthesis, rRNA maturation, telomere maintenance and glycolytic metabolism. Thus, our data indicate that high proteasome activity is coupled with other determinant biological processes of hESC identity.
Gesehen am 10.05.2019